Походження назв літописних слов'янських племен - Тищенко, К. (Народна творчість та етнографія, 2006)
The article researches ethnonyms of Slavonic Tribes, thus clearing some theories on etymology of Slavonic languages. A thorough research by O. Trubachov, which is discussed by the author as well, helped to systematize etymology of the names of the tribes.